Secrets of the sideshows - Nickell, Joe. (Lexington, Ky. : University Press of Kentucky, 2005)
On small-town ballfields and county fairgrounds, the sideshow performers set up their tents and trailers in the shadow of the Ferris wheel. There they amazed us with daring feats such as fire eating and sword swallowing, intrigued us with exhibitions of human oddities and various "anatomical wonders," and yes, deceived us with illusions such as "Atasha the Gorilla Girl" and even outright fakes. These bizarre spectacles engaged the mind as well as the eye. Was the human blockhead act, in which the performer pounded a large nail or ice pick into his nostril, real or fake? Was the so-called allig
Origins of the sideshow -- On the midway -- The ten-in-one -- Human oddities : large and small -- Human oddities : between a half and two -- Other human oddities -- Anatomical wonders -- Created oddities -- Working acts -- Illusions -- Animal shows -- Curios -- The egress.
Includes bibliographical references (pages 353-360) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Sideshows; Attractions (Spectacles); side shows; PERFORMING ARTS -- Circus; Sideshows; Schausteller; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.